Pembinaan Karakter Siswi Melalui Kitab Al-Akhlaq Lil Banat Jilid 1 - Ahmad Fauzi (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
Character education has several standard values that are each summarized in various definitions. As mentioned in the Diknas, that there are 18 character values that a nation should have, namely: Religious, Honesty, Tolerance, Discipline, Hard Work, Creative, Independent, Democratic, Curiosity, National Spirit, Love of the Homeland, Appreciating Achievement, Friendship/ communication, Peace love, Gemar Reading, Caring for the Environment, Social Care, and Responsibility. Kitab al-Akhlak lil Banat volume 1 by ustadz Umar bin Ahmad Baraja, a book containing moral guidance for the daughter students who are always in her writing always give knowledge and advice – advice, in the presence of the book al-akhlak lil banat is expected that the reader or student can respond to any stimulus given in the book of al-akhlak lil banat volume 1, then motivated to run and practice it. Gradually it becomes a good habit that will become a positive character for each student. The study of the book al-Akhlak lil Banat volume 1 was applied in Madarasah Ibtidaiyah Darussalamah Sumbersari to form the morality of students starting early because this lesson was applied in grades 4 and 5 madrasahs Ibtida'iyah.